Analysis of Internal and External Factors on Project Performance Based on Risk Management in Smelter Construction - Adi Pamungkas, Priyo; Susetyo, Budi (Universitas Ibn Khaldun Bogor, 2024)
The mining industry has projects that require effective risk management, especially in terms of smelter construction. Smelter construction is a complex process and requires attention to various internal and external factors that can affect project performance. This research uses quantitative research methods. In this study, the data collection method that will be used is a questionnaire technique. The data that has been collected is then analyzed using statistical analysis techniques using Structural Equation Modeling - Partial Least Square (SEM PLS). The results showed that the risk factors that obtained the most dominant value with a high risk category consisted of 8 indicators of internal and external risk factors, namely labor shortages, rising material prices, inexperienced project managers and experts, supplier changes close to project closure causing cost overuns, unclear project priorities where less important work is completed, uncertain weather, contaminated environment pollution, weather during construction activities. Internal and external factors together have a significant effect on project performance in terms of cost, quality and time in direct effect.